(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Present educational developments, the rise of the wise culture, social shifts and globalization, have affected higher education at a wider stage, culminating in the evolution of the teaching learning methods including immersive learning, quality improvement and quality assurance. Learning Management Method has now been applied to public establishments and businesses over two decades as part of a broad variety of ICT methods. The provided summary of this paper demonstrates the role of LMS in teaching and learning pedagogy, as well as connectivity and accessibility, and higher education institutions can incorporate the LMS into their learning method to achieve successful learning outcomes. It encourages users to observe meaningful learning across various design types, match individual Sneed, self-study and consumer experience meaningful learning through means of different models, match individual Sneed, self-study and promote lifelong learning. More specifically, the Learning Management Framework has provided convenient access and encouraged freedom to learn so you can learn from anywhere and at any time without any time and location limitations.